A successful start-up of an anaerobic membrane bioreactor (AnMBR) coupled mainstream partial nitritation-anammox (PN/A) system: A pilot-scale study on in-situ NOB elimination, AnAOB growth kinetics, and mainstream treatment performance. (1st December 2021) - Wu, Jiang; Kong, Zhe; Luo, Zibin; Qin, Yu; Rong, Chao; Wang, Tianjie; Hanaoka, Taira; Sakemi, Shinichi; Ito, Masami; Kobayashi, Shigeki; Kobayashi, Masumi; Xu, Kai-Qin; et al.
Highlights: A concept of AnMBR-PN/A process was proposed for mainstream treatment. In-situ FA/FNA exposure eliminated Nitrospira while retained Nitosonomas community. DO limitation prevented switch of the NOB community in the mainstream conditions. The effluent TN of the mainstream PN/A system was lower than 10 mg-N/L. Enhanced hydrodynamic shear force resulted in sludge settleability deterioration. Abstract: In this pilot-scale study, an innovative mainstream treatment process that couples the anaerobic membrane reactor (AnMBR) with a one-stage PN/A system was proposed for advancing the concept of carbon neutrality in the municipal wastewater treatment plant. This work demonstrates the start-up procedure of a pilot-scale one-stage PN/A system for mainstream treatment. The 255-day start-up of the one-stage PN/A system involved the cultivation of ammonium-oxidizing bacteria (AOB) from the activated sludge, suppression of nitrite-oxidizing bacteria (NOB), investigation of in-situ growth kinetics of anammox bacteria (AnAOB), and the 50-day operation of the pilot-scale AnMBR-PN/A process for natural mainstream treatment. It is verified in the pilot-scale system for the first time that the in-situ free ammonia (FA) and free nitrous acid (FNA) exposure could effectively eliminate the Nitrospira (the NOB genus) while retaining the Nitosonomas (the AOB genus) community in the suspended sludge. NOB community rebounding was not detected even at the mainstream conditions with low nitrogen concentrations (Influent ammonium concentration=38±6 mg-NH4 + -N/L) by intermittent aeration to control the system dissolved oxygen (DO) below 0.5 mg/L. The results of the mainstream treatment showed that the average effluent total nitrogen (TN) in the coupled process was generally lower than 10 mg-N/L, which meets the discharge limits of most prefectures in Japan. The investigated results of the in-situ anammox bacteria (AnAOB) growth kinetics suggested that the promoted start-up strategy of taking advantage of the warm months with higher mainstream temperature to achieve the rapid in-situ growth of the AnAOB is applicable in the investigated regions. From the perspective of the removal performance of the TN and organic substance, the AnMBR-PN/A process has great potential as the layouts of the carbon-neutral mainstream wastewater treatment plants. Graphical abstract: Image, graphical abstract